2023
DOI: 10.1021/acscentsci.2c01190
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Discovery of Small Molecule Modulators Targeting the Achilles’ Heel of SARS-CoV-2 Spike Protein

Abstract: The spike protein of SARS-CoV-2 has been a promising target for developing vaccines and therapeutics due to its crucial role in the viral entry process. Previously reported cryogenic electron microscopy (cryo-EM) structures have revealed that free fatty acids (FFA) bind with SARS-CoV-2 spike protein, stabilizing its closed conformation and reducing its interaction with the host cell target in vitro. Inspired by these, we utilized a structure-based virtual screening approach against the conserved FFA-binding po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Based on the conformation motion between the RBD and the subdomain 1 (SD1)–subdomain 2 (SD2) junction, Qian Wang et al designed the compound CPD7 using a structure-based virtual screening approach, which can insert between SD1 and SD2 of the S trimer to impede RBD opening to the up state, and its inhibition effect was experimentally evaluated by RT-PCR and SPR methods [ 8 ]. In addition, the cryo-EM structure revealed that compound SPC-14 could shift the conformation of S trimer toward the closed state [ 9 ]. Recently, the work of Carla Zannella et al further proved that this approach is reliable.…”
Section: Results and Disussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the conformation motion between the RBD and the subdomain 1 (SD1)–subdomain 2 (SD2) junction, Qian Wang et al designed the compound CPD7 using a structure-based virtual screening approach, which can insert between SD1 and SD2 of the S trimer to impede RBD opening to the up state, and its inhibition effect was experimentally evaluated by RT-PCR and SPR methods [ 8 ]. In addition, the cryo-EM structure revealed that compound SPC-14 could shift the conformation of S trimer toward the closed state [ 9 ]. Recently, the work of Carla Zannella et al further proved that this approach is reliable.…”
Section: Results and Disussionmentioning
confidence: 99%
“…Low molecular weight compound may be an effective way to prevent the viral attachment and infection. In fact, some compounds that interact with the S RDB, receptor ACE2, and RBD-ACE2 binding interface have shown antiviral potential, such as arbidol, CPD7, and polymerase inhibitor SPC-14 [ 7 , 8 , 9 ]. However, a number of various mutations have been reported in the binding pocket of RBD (located between S338 to Q506), which are responsible for the altered interactions with human receptors, resulting in resistance to existing vaccines, antibodies, and agents [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cryo-EM structure for SPC-14 shows a different interaction pattern with LA, as SPC-14 is further buried in the pocket, and hydrophobic stabilizing interactions are prominent, particularly with the nitro group having π-stacking interaction with Phe338 . Although no interactions are directly established with the hydrophilic portion of the site, the carboxylic acid remains at a distance of 6 Å from hydrophilic residue Arg408 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to lifitegrast and LA, SPC-14 has also been confirmed to bind the FABP, although no inhibition assays on the interaction between the S protein and ACE2 have been reported. 47 Binding was determined in SPR assays with the S protein, resulting in a binding affinity (KD) of 9.5 μM, with further cryo-EM structural determination confirming binding and clarifying how this compound binds to the FABP (Figure 8). 47 The cryo-EM structure for SPC-14 shows a different interaction pattern with LA, as SPC-14 is further buried in the pocket, and hydrophobic stabilizing interactions are prominent, particularly with the nitro group having π-stacking interaction with Phe338.…”
Section: Compounds Interacting With the Fabpmentioning
confidence: 98%
See 1 more Smart Citation